Nurse following hospital robot with special wheels and sensor intergration - Ramachandran, Nagarajan, Prof. Dr.; Bukhari, Illias; Awang Sabri, Awang Omar; Muhammad Asyraf, Abdul Rahman (Malaysian Association of Research Scientists (MARS), 2012)
The 10th Malaysian Technology Expo 2011 was organized by Malaysian Association of Research Scientists (MARS) and Professional Trade Exhibition and Meeting Planner (PROTEMP), 17th - 19th February 2011 at Kuala Lumpur Convention Centre (KLCC).